PERAN GURU BIMBINGAN KONSELING DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK KELAS X SMK TI AIRLANGGA SAMARINDA - Muhammad Reza Syah Fahlevi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was conducted based on the background that students have low learning interest in class X of SMK TI Airlangga. Learning interest is an interest in learning that encourages individuals to study and pursue learning. This study aims to determine: (1) the role of guidance counselors in increasing student learning interest, and (2) the obstacles faced by guidance counselors in increasing student learning interest. This study used a qualitative descriptive method with five research subjects, namely: a guidance counselor, three students, and a homeroom teacher. Data collection techniques included observation, interviews, and documentation. The analysis techniques used were: (1) data reduction, (2) data presentation, and (3) conclusion drawing. Based on the research results, it was found that: (1) The role of guidance counselors in increasing students' interest in learning is very important, (2) The obstacles faced by guidance counselors are difficulty in contacting students, inability to meet students face-to-face, and lack of cooperation from students' parents, and (3) Guidance counselors play an important role in increasing students' interest in learning.